Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00127-016-1254-z
|View full text |Cite
|
Sign up to set email alerts
|

Life-stress and reactivity by gender in a longitudinal birth cohort at 30 and 35 years

Abstract: These findings are consistent with a growing body of evidence indicating that some life events including interpersonal problems, illness/death and pregnancy/parenthood may be intrinsically more distressing for women. Detection of life event distress is important to aid in the prevention of mental/physical health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…In particular, a meta-analysis of 119 studies published between 1960 and 1996 found that women consistently reported greater exposure to stressful events than men across domains, including in both interpersonal and work domains (Davis et al 1999). It is possible that changing sociocultural norms regarding women in the workplace have closed the gap in work-related stressor exposure, as women place more importance on employment and financial success now than they did in the past (e.g., McLeod et al 2016).…”
Section: Fact 10: Different Types Of Stressful Events Influence Womenmentioning
confidence: 99%
“…In particular, a meta-analysis of 119 studies published between 1960 and 1996 found that women consistently reported greater exposure to stressful events than men across domains, including in both interpersonal and work domains (Davis et al 1999). It is possible that changing sociocultural norms regarding women in the workplace have closed the gap in work-related stressor exposure, as women place more importance on employment and financial success now than they did in the past (e.g., McLeod et al 2016).…”
Section: Fact 10: Different Types Of Stressful Events Influence Womenmentioning
confidence: 99%
“…Research on the sociology of health also has shown that stressor exposures and poorer health outcomes are unequally distributed in the population, varying by demographic factors, including gender and race [34,35], and that vulnerability to poorer health outcomes as a result of stressor exposure varies by gender and race [36][37][38]. Accordingly, gender and race are important factors to consider in examining pain and stressors among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation that the association between participation in the FF intervention and parents' CRP levels eight years later was conditioned on gender is also in concordance with prior research. Several studies focused on psychosocial outcomes suggest greater psychosocial stress during the transition to parenthood among mothers compared to fathers (24,27) and lower levels of postpartum depressive symptoms among mothers but not fathers 3.5 years after participating in the FF intervention (22). It is possible that the nature of the FF intervention, which encourages parents to work together as a coparenting team, may help explain why there appear to be particularly strong benefits among women (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas working fathers may be praised for their parental involvement, these same behaviors may be expected of motherhood and go unnoticed and unrewarded (34). Given the challenges associated with the transition to parenthood, especially among mothers (27), greater paternal involvement (via coparenting) and fathers' reinforcement of mothers' parental self-efficacy may buffer mothers from the potential physiological costs resulting from parenting stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation